Restructuring Measured Fishing Policy: Integrative Supervision of Fishery Business Actors in Realizing a Sustainable Blue Economy - Jumantoro, Tegar Raffi Putra; Supriantoro, Nadhila Citra; Albanna, Syedna Ahmad; Novemyanto, Alfin Dwi (Alauddin Law Development Journal, 2025)
Indonesia as a maritime country faces serious challenges in the problem of overexploitation and declining fish stocks in the management of marine resources in 11 Fisheries Management Areas (WPP). The quota-based Measured Fishing (PIT) policy has not been effective due to conflicts with local fishermen and weak supervision by the Ministry of Marine Affairs and Fisheries (KKP), as evidenced by violations of fishing zones by large and foreign vessels. This normative legal research uses a statutory, conceptual, and comparative approach. The results of the study show challenges in supervision and law enforcement. Several countries have used sophisticated technology and quota systems to manage fishing zones, but Indonesia faces obstacles in supervision. Researchers recommend the implementation of a satellite monitoring system, additional criminal sanctions, strengthening inter-agency coordination, and a customary-based sea closure system to restore fish stocks.